2012
DOI: 10.1371/journal.pone.0032861
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Analysis between HLA-DRB1 Shared Epitope Alleles and MHC Class II Transactivator CIITA Gene with Regard to Risk of Rheumatoid Arthritis

Abstract: HLA-DRB1 shared epitope (SE) alleles are the strongest genetic determinants for autoantibody positive rheumatoid arthritis (RA). One of the key regulators in expression of HLA class II receptors is MHC class II transactivator (CIITA). A variant of the CIITA gene has been found to associate with inflammatory diseases.We wanted to explore whether the risk variant rs3087456 in the CIITA gene interacts with the HLA-DRB1 SE alleles regarding the risk of developing RA. We tested this hypothesis in a case-control stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Moreover, the most protective, susceptible alleles were identical in both methods, illustrating the usefulness of the DISH method in looking for the most significant alleles in HLA fine-mapping studies. The observed associations of HLA-DRB1 alleles with RA or SLE in DISH-based and HMM-based approaches were supported by previous studies 15,16 that tested for the association for sequenced HLA-DRB1 alleles.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, the most protective, susceptible alleles were identical in both methods, illustrating the usefulness of the DISH method in looking for the most significant alleles in HLA fine-mapping studies. The observed associations of HLA-DRB1 alleles with RA or SLE in DISH-based and HMM-based approaches were supported by previous studies 15,16 that tested for the association for sequenced HLA-DRB1 alleles.…”
Section: Discussionsupporting
confidence: 77%
“…Another study showed that the two SNPs rs4774 and rs6498122 of CIITA were associated with oral lichen planus (OLP) 28 . CIITA//rs8048002 was found to be associated with RA in a Swedish cohort 29 . CIITA//rs12932187 and rs11074938 were found to be susceptibility markers of nasal passages inflammation in asthma patients in a Japanese population 30 .…”
Section: Discussionmentioning
confidence: 92%
“… 5 26 Seropositivity with either positive RF or anti-CCP or antinuclear antibodies had been associated with higher mortality from CHD even in patients without articular symptoms. 27 28 This comparison of autoantibody-positive RA to autoantibody-negative RA is relevant given that the genetic contribution of HLA-DRB1 shared epitope is restricted to autoantibody-positive RA, 29 30 which had also been associated with higher cardiovascular mortality rate. 31 Like the aforementioned studies, our study showed an association between seropositivity and MI risk.…”
Section: Discussionmentioning
confidence: 99%